Women's Political Empowerment A New Global Index, 1900-2012 - Sundström, Aksel (World development, 2017)
The political empowerment of women is a societal process crucial to development and progress. The V-Dem women's political empowerment index (WPEI) provides information about women's civil liberties, civil society participation, and political participation globally. Spanning from 1900 to 2012, three dimensions of empowerment, and over 170 countries, it is among the most comprehensive measures of women's empowerment available. This paper presents a conceptualization of women's political empowerment and provides an overview of the construction of the index and operationalization of its three sub-dimensions: Women's civil liberties, civil society participation, and political participation. Compared to other indices measuring women's empowerment, such as the GDI, the GEM, the GII, and the CIRI data on human rights, the V-Dem index allows more precise measurement and is superior in temporal scope and coverage of countries of the Global South. The paper demonstrates the benefits of this new index and its sub-dimensions through several empirical illustrations